Этнографичeские материалы в работе Езника Кохбаци «О провержение ересей» - Хостикян, Мисак (Институт языкознания РАН)
In 2000, during one of his lectern conversations, an outstanding philosopher and linguist Edmon Avetyan pronounced: “As far I know, Misak Khostikyan was the last philosopher in the country of Armenia. He was executed by a firing squad in 1938. No philosopher ever appeared in my sight in Armenia afterwards”. Mentioning the names of Grigor Narekatsi, David the Invincible, and Hovhan Yerznkatsi of ancient glory, Avetyan summed up: “I don’t know whether contemporary Armenia has any philosophers of value or not. Armenians are not a nation of philosophers; they are rather a nation of poets”. As for the current article, Ethnographic Materials in Yeznik Koghbatsi’s “Refutation of Heresies”, published in 1916 in the “Armenian Ethnographical Bulletin” in Tiflis, it’s value is self evident. We believe that this article will be of great interest for the Armenian Bulletin’s readers.
Keywords: Литература